2016
DOI: 10.1002/cpdd.281
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Effects of Isavuconazole Coadministration With the Cytochrome P450 Enzyme Substrates Bupropion, Repaglinide, Caffeine, Dextromethorphan, and Methadone in Healthy Subjects

Abstract: This report describes phase 1 clinical trials performed to assess interactions of oral isavuconazole at the clinically targeted dose (200 mg, administered as isavuconazonium sulfate 372 mg, 3 times a day for 2 days; 200 mg once daily [QD] thereafter) with single oral doses of the cytochrome P450 (CYP) substrates: bupropion hydrochloride (CYP2B6; 100 mg; n = 24), repaglinide (CYP2C8/CYP3A4; 0.5 mg; n = 24), caffeine (CYP1A2; 200 mg; n = 24), dextromethorphan hydrobromide (CYP2D6/CYP3A4; 30 mg; n = 24), and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…The modest increase in R-warfarin exposure was likely caused by inhibition of CYP3A4, rather than CYP1A2, because isavuconazole is an established moderate inhibitor of the CYP3A4 enzyme, 7 but it did not affect the exposure of the CYP1A2 substrate caffeine. 9 The findings of the present study also demonstrate that clinically targeted doses of isavuconazole do not inhibit CYP2C9-mediated metabolism in vivo. By comparison, the antifungal agent fluconazole is an in vitro inhibitor of CYP2C9 and CYP3A4 13,14 but not of CYP1A2.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The modest increase in R-warfarin exposure was likely caused by inhibition of CYP3A4, rather than CYP1A2, because isavuconazole is an established moderate inhibitor of the CYP3A4 enzyme, 7 but it did not affect the exposure of the CYP1A2 substrate caffeine. 9 The findings of the present study also demonstrate that clinically targeted doses of isavuconazole do not inhibit CYP2C9-mediated metabolism in vivo. By comparison, the antifungal agent fluconazole is an in vitro inhibitor of CYP2C9 and CYP3A4 13,14 but not of CYP1A2.…”
Section: Discussionsupporting
confidence: 60%
“…5,6 Its active moiety, isavuconazole, has been confirmed as a sensitive substrate and moderate inhibitor of cytochrome P450 as well as multidrug and toxin extrusion 1 in healthy human subjects. [8][9][10] Studies conducted in vitro suggest that isavuconazole also has inhibitory potential for CYP1A2 and CYP2C9. In human liver microsomes, the inhibition constant (IC 50 ) for phenacetin-O-dealkylase activity of CYP1A2 was 38.5 μmol/L, and the K i for diclofenac 4 -hydroxylase activity of CYP2C9 was 8.6 μmol/L (data on file).…”
mentioning
confidence: 99%
“…Compared to voriconazole and liposomal amphotericin B, it offers some advantages including good tolerability, a lower side effect profile, 29 excellent bioavailability (switch from IV to oral treatment), 27 and reduced drug–drug interactions. 49 , 84 , 85 In the Phase III SECURE trial, isavuconazole demonstrated similar efficacy to voriconazole for the treatment of IA. 29 Recent guidelines recommend isavuconazole as gold standard treatment (together with voriconazole) for IA in patients with hematological malignancies.…”
Section: Conclusion and Place In Therapymentioning
confidence: 99%
“…Important properties of isavuconazole in vivo include the lack of an effect of food on absorption for the oral formulation, the lack of a potentially nephrotoxic solubilizing excipient for the IV formulation, the consistency of intersubject dose-exposure relationships, 3 and comparatively favorable drug-drug interaction profiles. [5][6][7][8][9][10] Isavuconazole has demonstrated noninferiority to voriconazole for the primary treatment of invasive mold disease 11 and has shown successful outcomes in patients with mucormycosis in phase 3 trials. 12 It was approved in 2015 by the US Food and Drug Administration for the treatment of adults with invasive aspergillosis and invasive mucormycosis and by the European Medicines Agency for treatment of adults with invasive aspergillosis and for mucormycosis in patients for whom amphotericin B is not appropriate.…”
mentioning
confidence: 99%
“…Isavuconazonium sulfate is available in water‐soluble oral and intravenous (IV) cyclodextrin‐free formulations. Important properties of isavuconazole in vivo include the lack of an effect of food on absorption for the oral formulation, the lack of a potentially nephrotoxic solubilizing excipient for the IV formulation, the consistency of intersubject dose‐exposure relationships, and comparatively favorable drug‐drug interaction profiles . Isavuconazole has demonstrated noninferiority to voriconazole for the primary treatment of invasive mold disease and has shown successful outcomes in patients with mucormycosis in phase 3 trials .…”
mentioning
confidence: 99%